Skeletal development during childhood and adolescence and the effects of physical activity - Kemper, H. C. (Pediatric Exercise Science, 2000)
This paper reviews the growth and development of skeletal mass in youth and the effects of physical activity upon the bone mass in young people. The different methods to measure the bone mass are described such as anthropometrics, radiographics, dual energy X-ray absorptiometry, quantitative computed tomography, and ultrasound. Two different mechanisms are important for the formation and plasticity of bone: a central hormonal mechanism (with estrogen production) and a local mechanism (based on mechanical forces of gravity and muscle contractions). This local mechanism is closely connected to physical activity patterns and therefore discussed in more detail. Thereafter the natural course of the development of the bone mass during youth is described, taking into account the pubertal stages of boys and girls and also the age at which the maximal bone mass (peak bone mineral density) will be reached. The last part is devoted to the effects of physical activity on bone mass based on results of randomized controlled trials. Although the number of experimental studies are scarce, significant effects of weight bearing activity and high impact strength training programs are shown on the side specific bone mineral density in both boys and girls.